His-containing plant metallothioneins: comparative study of divalent metal-ion binding by plant MT3 and MT4 isoforms - Tomas, Mireia (2014)
Metallothioneins (MTs) are a superfamily of Cys-rich, low-molecular weight metalloproteins that bind heavy metal ions. These cytosolic metallopeptides, which exist in most living organisms, are thought to be involved in metal homeostasis, metal detoxification, and oxidative stress protection. In this work, we characterise the Zn(II)- and Cd(II)-binding abilities of plant type 3 and type 4 MTs identified in soybean and sunflower, both of them being His-containing peptides. The recombinant metal-MT complexes synthesised in Zn(II) or Cd(II)-enriched Escherichia coli cultures have been analysed by ESI-MS, and CD, ICP-AES, and UV spectroscopies. His-to-Ala type 3 MT mutants have also been constructed and synthesised for the study of the role of His in divalent metal ion coordination. The results show comparable divalent metal-binding capacities for the MTs of type 3, and suggest, for the first time, the participation of their conserved C-term His residues in metal binding. Interesting features for the Zn(II)-binding abilities of type 4 MTs are also reported, as their variable His content may be considered crucial for their biological performance.